How sure am I? How text genre and question type shape comprehension calibration in primary and secondary school students - Zagato, Alessandra; Pizzigallo, Eleonora; Pellegrino, Gerardo; Capodieci, Agnese; Carretti, Barbara; Mirandola, Chiara (Frontiers in Psychology, 2026)
BackgroundMetacognitive skills in text comprehension are fundamental for students' learning, yet their development may differ depending on text genre (narrative vs. expository), question type (factual vs. inferential), and educational level. However, little is known about how these factors influence students' calibration of comprehension.MethodsThis study examined postdictive metacognitive judgments through student's confidence ratings collected after completing two reading comprehension tasks administered to 407 primary and secondary school students. These confidence judgements were then used to compute three calibration indices: Absolute Accuracy Index, Bias Index, and Discrimination Index, which assess the distance between the predicted and actual performance and the ability to discriminate correct from incorrect answers.ResultsAnalyses revealed that both primary and secondary school students performed similarly on narrative texts. However, primary school students scored significantly lower than secondary school students and overestimated their performance on expository passages and inferential questions. This pattern suggests that metacognitive calibration becomes more accurate with increased exposure to complex text genres and scholastic experience.ConclusionsThese findings highlight the influence of text genre and question type on metacognitive calibration and provide useful implications for educational practices aimed at fostering metacognitive skills—such as teaching genre-specific reading strategies and training students to reflect on their comprehension.